A Boy of Embers and Ash - Kealley, Adam (Curtin University, 2023)

(untitled)
This thesis utilises creative practice as a research methodology to explore the haunted condition of the Australian queer young adult subject through a novel, A Boy of Embers and Ash, and an accompanying exegesis, ‘Disturbances: the spectral condition of the Australian queer young adult’. It employs spectral theory to suggest an intersubjective relationship between queer youth and their ghostly historical forebears, proposing new possibilities for agency liberated from the imperative towards visibility and presence.